Species Richness and Diversity of Butterflies in Nagaland, North East Region of India - Yojana Patil; Shruti Kulkarni (Andalasian International Journal of Entomology, 2026)
The Northeast region of India is a hotspot of biodiversity, boasting one of the richest butterfly diversities in the Oriental region, particularly in endemic species. The Nagaland region, located in the north-eastern part of India, is renowned for its rich biodiversity. The place has a montane ecosystem, which means the butterflies here differ from those in other mountain terrains and remain understudied. The study focuses on cataloging and monitoring butterfly species from Aug 2021 to Aug 2023 in and around Nagaland. The survey is done by the simple checklist method. Observation is done using a simple visual method; data collection is via the transect method. The transect distance range was mainly 500 m to 1.5 km along the roadside or streamside. A total of 64 species of 6 families were recorded during the study. Among 6 families, Hesperiidae (8), Lycaenidae (10), Papilionidae (11), Pieridae (9), Nymphalidae (25), and Riodinidae (1) species were found in the study area. The study shows that the region is rich in butterfly diversity but understudied and in need of updated documentation. Therefore, continuous monitoring, research, and updating are significant for conservation and for mitigating the effects of changing climatic patterns and anthropogenic activities on butterfly diversity.